Barriers to the utilization of HIV/AIDS surveillance data in Mexico - Daniela C Rodríguez; Carlos Magis-Rodríguez; Enrique Bravo-García (Instituto Nacional de Salud Pública, 2013)
Objective. Qualitative study to identify and understand the barriers to using HIV/AIDS surveillance data experienced at the state level in Mexico. Materials and methods. Eighteen individuals were interviewed in Michoacán, Morelos and Mexico City, including representatives from government and non-government organizations. Transcripts were analyzed thematically based on expected barriers to data utilization drawn from the literature. Results. Four categories of barriers were identified: knowledge and accessibility to existing data, limits on using data, decision-making barriers, and resource barriers. Discussion. This study highlights the factors that influence how local programs use surveillance data to improve their programmatic activities. Two specific areas are identified for potential improvements: awareness and accessibility of surveillance data available, and  improving local capacity of officials to use them.